Students' Descriptive Writing Ability Improvement through Six Thinking Hats Strategy - Dahlia Dahlia; Iskandar Iskandar; Maemuna Muhayyang (ARRUS Journal of Social Sciences and Humanities, 2024)
This research aims to find out whether or not the use of the six thinking hats strategy improves the students’ writing ability. It was conducted by using quantitative research with a quasi-experimental research design. Its’ population was the ninth-grade students of SMP Negeri 1 Tinambung randomly taken as the sample consisting of 46 students for both the experiment and control class. The research data were obtained by giving descriptive writing tests in the form of pre-and post-test to see the effect of the six thinking hats strategy on the students’ writing improvement and its results were analyzed using the SPSS program. The data analysis resulted that the six thinking hats strategy significantly improved the writing ability of ninth-grade students proved by the mean score of the students’ pre-test in which the experimental class was 44.96 and the control class was 47.39; the mean score of students’ post-test in which the experimental class was 83.26 and the control class was 62.91; the Sig (2 tailed) value is 0.000 < 0.05 meaning that H0 was rejected and H1 was accepted. These findings conclude that the six thinking hats strategy was able to be used to effectively improve the students’ descriptive writing text.